Linguistic Picture of the World of Lesya Ukrainka`s Epistolary (Linguostylistic Studies, 2014)
Today the linguistic resources of emotional, internal, psychological state of word masters` achieve special urgency by means of their epistolary heritage’s research that is often considered as peculiar tool of the writer’s creativity.Article is devoted to the research of the linguistic epistolary genre of Lesya Ukrainka in the context of national-language picture of the world through which the completeness and variety of linguistic expression is revealed by the writer.It was made an attempt to investigate the comprehensive study of lingual-stylistic features of Lesya Ukrainka`s letters in a complex way. The allocation of general and special requests (social honorifics, anthroponyms, nonce words), individual author growths state colloquial and foreign folk elements is applied.Some linguo-stylistical features are identified. The basic ways of naming the recipients are defined, which is the effective method of expressing the author's point of view and an important linguistic resource with broad expressive possibilities. Key words: epistolary, language creation, honorifics, nonce words, anthroponyms, linguistic picture of the world. References